Reconstruction of the longitudinal phase portrait for the SC CW heavy ion HELIAC at GSI. (November 2019) - Lauber, S.; Aulenbacher, K.; Barth, W.; Burandt, C.; Dziuba, F.; Forck, P.; Gettmann, V.; Heilmann, M.; Kürzeder, T.; List, J.; Miski-Oglu, M.; Podlech, H.; et al.
Abstract: At the GSI Helmholtzzentrum für Schwerionenforschung (GSI) in Darmstadt, Germany, the HElmholtz LInear Accelerator (HELIAC) is currently under construction. The HELIAC comprises superconducting multigap Crossbar H-mode (SC CH) cavities. The input beam is delivered by an already existing High Charge Injector (HLI). For the further development of the accelerator a detailed knowledge of the input beam parameters to the SC section is necessary. A method for beam reconstruction is incorporated, which provides for longitudinal beam characteristics using measurements with a beam shape monitor and a particle simulation code. This finalizes the investigations on 6D beam parameters, following previous measurements in transversal phase space. The reconstruction of the longitudinal phase portrait is presented.